Characterizing biomass combustion emission contributions to ambient aerosol concentrations - Engling, Guenter, author; Collett, Jeff, advisor; Kreidenweis, Sonia M., committee member; Henry, Charles, committee member; Denning, A. Scott, committee member (Colorado State University. Libraries, 2006)
Atmospheric aerosol particles are known to exert significant effects on air quality, human health, ecosystem health, visibility, and the radiative balance of the atmosphere. Because of their relatively long lifetimes, the influence of submicron (fine) aerosol particles can be exerted far downwind of their source. Biomass combustion is a major global source of atmospheric fine particles and organic matter in particular. Quantifying the impacts of biomass combustion aerosol far from its source is difficult, but is a national priority given the frequency of fires in several parts of the U.S. and federal land manager plans to increase prescribed burning in the coming years. In recent years the most common approach to apportioning ambient carbonaceous aerosol among different source types has involved the use of organic molecular markers which serve as source specific tracers. The most popular tracer for biomass combustion is levoglucosan, a combustion product of cellulose. Traditional methods for measuring levoglucosan involve organic solvent extraction, chemical derivatization, and Gas Chromatography-Mass Spectrometry (GC-MS) analysis of aerosol filter samples collected over periods of 24 hr or more. This analytical approach is labor intensive and expensive, precluding its widespread use in routine air quality monitoring networks. In addition, source profiles for biomass combustion, are mostly limited to residential wood combustion sources, leaving a need for new emissions profiles characteristic of wild and prescribed fires, which bum a greater mix of fuel types under a wide range of conditions. The research presented here consists of three primary efforts: (1) development of simpler, less expensive techniques for measurement of levoglucosan and other biomass combustion products, (2) examination of the contributions of biomass combustion to ambient aerosol at a typical visually protected environment in the western U.S. (Yosemite National Park), and (3) examination of the variability in source marker emission profiles for a variety of fuel types burned under a range of conditions characteristic of those expected in wild and prescribed fires. Three alternative measurement techniques that are sensitive and precise, yet cost effective and easy to use, were explored and optimized for the determination of biomass combustion source tracers: high performance anion exchange chromatography, micro-chip capillary electrophoresis, and an enzyme biosensor. Sources of high summertime concentrations of organic aerosol in the western U.S. were investigated during the Yosemite Aerosol Characterization Study conducted in the summer of 2002. Primary contributions of biomass smoke to fine particle organic carbon were estimated to be as high as 100% on selected days due to the influence of local fires in addition to fires prevailing in Southern Oregon and other parts of California. High concentrations of monoterpene oxidation products and other organic compounds of secondary origin also indicated a significant contribution of secondary organic aerosol to ambient fine particle concentrations. An important portion of secondary species was likely associated with smoke from biomass combustion. Emission signatures of carbonaceous material from the open combustion of biofuels were determined as a function of combustion conditions. Emissions of biomass combustion tracers showed a wide range of values as a function of fuel type and combustion conditions. Levoglucosan emission factors for the same combustion conditions differed between individual types of biomass by one order of magnitude, while combustion phase and bum direction generally resulted in variations between emission factors on the order of 2 to 3 for the same fuel type. The need for more detailed emission profiles of molecular source tracers, reflecting the various combustion conditions that are characteristic of wildfires and prescribed bums, was demonstrated.
Keywords: analytical chemistry